2019
DOI: 10.1002/chem.201902962
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach to Regio‐ and Stereodefined Fully‐Substituted Alkenylsilanes by Pd‐Catalyzed Allenic C(sp3)−H Oxidation

Abstract: A highly efficient palladium‐catalyzed functionalization of allenylsilanes to give regio‐ and stereodefined fully‐substituted alkenylsilanes has been developed. This oxidative coupling reaction showed good functional group compatibility with exclusive regio‐ and stereoselectivity. The pending olefin on the silyl group was shown to be an indispensable element for the initial allenic C(sp3)−H bond cleavage, and performs as the directing group to control the overall selectivity. The addition of substoichiometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Further studies suggested that the olefin moiety in the chlorosilane is necessary to the present NiH-catalyzed coupling reaction (Table S14, ESI†). 17…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies suggested that the olefin moiety in the chlorosilane is necessary to the present NiH-catalyzed coupling reaction (Table S14, ESI†). 17…”
mentioning
confidence: 99%
“…Further studies suggested that the olefin moiety in the chlorosilane is necessary to the present NiH-catalyzed coupling reaction (Table S14, ESI †). 17 To illustrate the synthetic applicability of the present method, the gram-scale reaction was investigated (Scheme 5). Interestingly, a 10 mmol scale reaction could afford 3a in 75% yield.…”
mentioning
confidence: 99%